Electrochemical behavior of copper electrolysis effluent - Arias Arce, Vladimir (2010)
Study of the electrochemical behavior of copper allows us to identify and characterize the partially ionic nature of the aqueous solubility of impurities in the mass of ore bodies of metallic materials of copper mineral species and therefrom obtain sequences in the identification and effluent characterization activity hydrometallurgical mineral content with valuable copper. The absorption spectra determninación compounds with metal cores in the range from UV Visible acids sulfur containing base metals means enabling the implementation of the sequential separation of elements and species which are considered deleterious and denote pollution, acting against environmental sustainability.